A field guide to selected tress, shurbs and herbs of the Tangsibji hydro energy project area / (Acc: 1869) - National Biodiversity Centre, MoAF.; Nima Gyeltshen, Sangay Dema, Kezang Tobgay, Tandin Wangchuk and Choki Gyeltshen (Serbithang, Thimphu : National Biodiversity Centre, 2017)
This publication is the outcome of more than two years offield work carried out as part of the collaborative project "Rescue and Rehabilitation of threatened and rare plant species from 118 MW Nikachu Hydropower project sites for long-term conservation and development of national repository of botanical information" between"Tangsibji Hydropower Energy Limited(THyE) and the national Biodiversity Centre(NSB), Ministry of Agriculture and Forests (MoAf).
Keywords: Plant species--Rescue and rehabilitation-- Bhutan